A retrospective study on the surgical management and outcome of congenital diaphragmatic hernia in neonates - Gulshan, Javaid Iqbal; Raina, Sanjay; Wani, A. Hamid (International Journal of Research in Medical Sciences, 2024)
Background: Congenital diaphragmatic hernia is a developmental disorder in the anatomy of the diaphragm, which can range from the presence of a thin sac to the frank absence of part of the diaphragm. It results in protrusion of abdominal contents in the chest. CDH once considered as a surgical emergency is no longer a valid dictum. But definitive management of CDH is the surgical correction of defect. Study the demographics, presentation, diagnosis, and surgical outcomes of congenital diaphragmatic hernia (CDH) repair without significant associated congenital anomalies at a tertiary care institute. Methods: This was a retrospective study over 3 years from January 2021 to December 2023. Data was collected and noted from the medical records department. Patient’s clinical data in terms of demography, presentation, radiology, preoperative condition, timing of surgery after admission, intra-operative findings and post-operative course (including postoperative complications, duration of NICU stay, the incidence of sepsis, and need of inotropes), etc. Results: Most patients were male (85%). Among the total cohort, 70% were born outside the tertiary care institute and were referred from peripheral hospitals. Respiratory distress was the predominant complaint (85%). Congenital diaphragmatic hernia (CDH) was incidentally discovered in 5% of neonates. The majority of patients (70%) underwent surgical intervention between the 3rd postnatal day and up to one week. Left-sided herniation was observed in 90% of cases. An identifiable hernial sac was found in 18% of patients, with part or the entirety of the stomach being the most frequently encountered herniated viscera. Conclusions: Congenital diaphragmatic hernia (CDH) presents as a significant congenital anomaly in the pediatric surgery domain. Hidden mortality in case of CDH leads to underreporting of the actual incidence of the condition. The success of surgical intervention depends on a myriad of factors, encompassing patient-specific attributes and surgical methodologies. However, instances devoid of overt congenital anomalies and featuring stable preoperative physiological parameters typically yield satisfactory surgical outcomes, with favorable results.